2012
DOI: 10.1016/j.lisr.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Young adults and everyday-life information: The role of news media

Abstract: There is a paucity of research examining the everyday-life information seeking of young people, especially investigating the role that the news media has in providing information to young people for use in their everyday lives. A qualitative, interpretivist approach is adopted, involving 34 students, ages 18 to 25, from an Australian university. First, 20 students were interviewed about their news seeking (including topics and sources). Then 14 students participated in verbal protocol analysis, which involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 19 publications
(57 reference statements)
1
22
0
Order By: Relevance
“…Users on SBNs are influenced by celebrities, experts and leaders, as that (i) increases the users' reputation in social and professional networks (Kane et al 2014) (ii) provides indirect connections, which are not possible in offline environments, and (iii) keeps users informed of CELs personal, social and professional lives in real time. A study by Williamson et al (2012) on young users' news activities on Facebook finds that users prefer personal news in the form of information posted by friends or through status updates and reporting issues and events in real time (e.g. Facebook status update -Raining heavy, homes likely flooded).…”
Section: User Influencementioning
confidence: 99%
See 3 more Smart Citations
“…Users on SBNs are influenced by celebrities, experts and leaders, as that (i) increases the users' reputation in social and professional networks (Kane et al 2014) (ii) provides indirect connections, which are not possible in offline environments, and (iii) keeps users informed of CELs personal, social and professional lives in real time. A study by Williamson et al (2012) on young users' news activities on Facebook finds that users prefer personal news in the form of information posted by friends or through status updates and reporting issues and events in real time (e.g. Facebook status update -Raining heavy, homes likely flooded).…”
Section: User Influencementioning
confidence: 99%
“…Facebook status update -Raining heavy, homes likely flooded). A respondent in the study by Williamson et al (2012) says, "I suppose from blogs and Facebook and all those sorts of things, I get personal news, that I find out from other people" (Williamson et al 2012, p. 262). Based on the above, this study hypothesizes the relationship between user influence in SBNs and continuance of news consumption in the network as Hypothesis 2a: User Influence in a social broadcasting network will lead to greater continuance of news consumption in the network.…”
Section: User Influencementioning
confidence: 99%
See 2 more Smart Citations
“…It was found that younger students, undergraduates and people with more extroverted personalities tended to use these sites more frequently. Another study, conducted by Williamson, Qayyum, Hider, and Liu (2012), discussed the role of new media in young adults' (18 -25 years old) everyday life information-seeking behaviour. These findings showed that traditional print media was still an important source of information and social media was used to communicate with others rather than to seek information.…”
Section: Everyday Information Behaviourmentioning
confidence: 99%